HEALTH AND MINING PRACTICES IN INDIGENOUS TERRITORIES - Will da Silva Pacheco; Dayanne de Nazaré dos Santos; Monique Teresa Amoras Nascimento; Deisiane da Silva Mesquita; Karytta Sousa Naka; Nádile Juliane Costa de Castro (Cogitare Enfermagem, 2024)
Objective: To identify the repercussions of mining practices on Indigenous Territories on health.